Antibacterial Activity of Reduced Silver Leaf Extract of Ketumpang Air (Peperomia pellucida (L.) Kunth) Against Staphylococcus aureus - Efendi, Tania Tiara; Miswanda, Dikki; Nasution, M Pandapotan; Lubis, Minda Sari; Hermanto, Bambang (Pustaka Media Publishing, 2023)
Silver particles are widely applied in various medical fields, one of which is as an antibacterial. The advantage of silver particles is their small particle size, which increases their antibacterial effect. One of the environmentally friendly methods that can be used to synthesize silver particles is by utilizing extract of daun ketumpang air (Peperomia pellucida (L.) Kunth) through a reduction reaction. The aim of this research was to determine the antibacterial activity of silver particles made using water ketumpang leaf extract against Staphylococcus aureus bacteria. Silver particles were synthesized using the green synthesis method from extract of daun ketumpang air (Peperomia pellucida (L.) Kunth) which acts as a bioreductant. Silver reduction using water ketumpang leaf extract was carried out with varying concentrations of AgNO3 solution of 1 mM, 2 mM, 5 mM, and 10 mM with a ratio between the extract and AgNO3 solution of 1:40. The resulting silver particles were characterized using a Uv-Vis spectrophotometer and particle size analysis using PSA. The antibacterial activity test of the reduced silver particles was carried out against Staphylococcus aureus bacteria using the Kirby-Bauer method. The results of the research showed the formation of silver particles in the form of a change in the color of the solution from yellow to brownish. Analysis using a UV-Vis spectrophotometer showed a maximum wavelength of 423 nm, which indicated that silver particles were formed. The results of PSA analysis show the size of silver particles, where the smallest size of silver is 0.41 μm for a concentration variation of 10 mM. The antibacterial activity test showed strong antibacterial activity against Staphylococcus aureus bacteria with an average diameter of the inhibition zone of 11.48 mm. This shows that ketumpang water leaf extract can be used as a bioreductant in reducing silver particles and the silver particles produced have the potential to be antibacterial.